Policy Challenges for Agriculture and Rural Areas in Norway - Hemmings, Philip (OECD Economics Department Working Papers, 2016)
Norwegian policy gives high priority to supporting rural communities, with support for agriculture receiving particular attention. It is broadly successful in terms of maintaining rural communities, and urban-rural gaps in a range of well-being indicators are comparatively narrow. However, the cost-efficiency and sustainability of the policy mechanisms are questionable. Agriculture and rural policy in Norway needs to focus more strongly on economic sustainability alongside social sustainability. Agricultural support remains overly concentrated on maintaining the status quo and has seen little reform compared with policies elsewhere in the OECD. In contrast, the fishing industry has reformed much further towards economic sustainability, aquaculture has seen considerable success and there is potential for more rural tourism. Supporting rural communities also requires attention to the quality of public services in rural areas, and this report draws particular attention to inefficiencies arising from small-scale municipalities, and supports efforts to encourage mergers towards larger units, paving the way for greater operational leeway for municipal government.This working paper relates to the 2016 OECD Economic Survey of Norway (www.oecd.org/eco/surveys/economic-survey-norway.htm)